Podonomus amarali n. sp., a new species of the albinervis group (Diptera: Chironomidae: Podonominae) from Atlantic Forest, southern Brazil - Pinho, Luiz Carlos; Shimabukuro, Erika Mayumi (Zootaxa, 2018)
Podonomus amarali sp. n. is described from male, female, larva and pupa collected in the Brazilian Atlantic Highlands. The new species belongs to the albinervis group, which comprises eight Andean species.